A IMPORTÂNCIA DA FAMÍLIA NO TRATAMENTO DA MULHER ACOMETIDA COM CÂNCER DE MAMA - Moraes, Yasmim Lima de; Silva, Egnaldo Manoel da; Souza, Maxsuel Oliveira de; Silva Neto, Luiz Wilson Machado da Costa e (Gep News, 2017)
Tipo de Apresentação: Pôster